PENGGUNAAN APLIKASI ADOBE ANIMATE CC DALAM MENDESAIN MULTIMEDIA INTERAKTIF BERBASIS KONFLIK KOGNITIF MATERI ALAT-ALAT OPTIK - Ina, Felina Ardini; Mufit, Fatni (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2022)
Certain of research show that misconceptions be found in the material of optical instrument. The use of interactive multimedia is also lacking in supporting 21st-century learning. This study aims to produce an interactive multimedia design based on cognitive conflict using adobe animate cc valid optical tools. The stage of this research includes the preliminary research and development stage or prototyping, which is limited to expert review evaluation. Data sources were obtained from questionnaires, journal analysis, and validation of experts by three physics lecturers. The data analysis technique uses percentages and the V’aiken formula. Preliminary research found that student's understanding of concepts was low on optical instruments, and IT-Based teaching materials were not available to improve conceptual understanding. In the development or prototyping phase, interactive multimedia has been designed according to the syntax of the cognitive conflict-based learning model. The results of the self-evaluation were obtained with excellent criteria. The validity results in the test obtained an average of 0.86 with a very valid category. They concluded that interactive multimedia based on cognitive conflict, especially on the material of optical devices, is valid with aspects of material substance, material design, learning design, visual communication display, and software use.